CHARACTERIZATION OF PHENYLALANINE AMMONIA LYASE PURIFIED FROM LOCALLY CULTIVATED GRAPE SEEDS (Vitis vinifera L.) - S. Y. Hadeel; S. A. Khalida (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to investigate certain characteristics of the purified Phenylalanine ammonia lyase (PAL). The results revealed that the molecular weight was 180 kDa by gel filtration and Native-PAGE. The optimal pH and temperature for enzyme activity were 7 and 40 °C respectively. The enzyme activity was stable against pH values range of 6-8. The enzyme retained 79% of its total activity after incubation for one hour at 50 °C and retained 7% (lost 93%) of its activity at 70 °C. The entire activity was completely lost when the enzyme was incubated for 1 hour at temperatures over 70 °C. Carbohydrate content of the purified enzyme was estimated to be 24.61%. Km, Kcat and Vmax were estimated with phenylalanine as substrate, the values were 0.021 mM, 20.67 sec-1 and 4.13 mM/min respectively.